How catching the interstellar wind in the inner solar system led the way on a road to interdisciplinary research between heliophysics and astrophysics - Möbius, Eberhard (Frontiers in Astronomy and Space Sciences, 2023)
At this juncture, combined in-situ observations of the interstellar wind through the solar system and of their pickup ions, implanted after ionization into the solar wind, tell us, in comparison with interstellar absorption lines of nearby stars, that the Sun is in an interaction region of the two nearest clouds. This new finding shakes the long-held understanding that we are inside the Local Interstellar Cloud. Here, we discuss how space physics evolved toward such interdisciplinary studies between heliophysics and astrophysics. In 1984, the discovery of interstellar He+ pickup ions opened the very local interstellar medium to in-situ diagnostics at 1AU. PUIs provide the interstellar gas composition and form a steppingstone for accelerating ions, especially into anomalous cosmic rays. Ulysses GAS enabled imaging of the interstellar wind for He, followed by IBEX-Lo for He, H, O, and Ne. Using the Sun as a gravitational spectrograph, the gas velocity vector and temperature at the heliopause follow from these observations. The all-sky images of the heliospheric boundary with energetic neutral atoms taken by IBEX revealed a bright Ribbon as a compass for the interstellar magnetic field near the Sun. Combining the interstellar gas flow, interstellar magnetic field, and secondary interstellar neutral He and O leads to a synergistic determination of the heliosphere’s shape, its interaction with the very local interstellar medium, and our surrounding radiation environment. The elemental and isotopic composition from PUI and neutral gas observations constrains the galactic evolution and Big-Bang-cosmology, opening multiple interdisciplinary research opportunities.